ANALISIS PROSES PEMBUATAN PATI UBI KAYU (TAPIOKA) BERBASIS NERACA MASSA - ARNIDA MUSTAFA (AGROINTEK, 2015)
Tapioca is starch that is extracted from cassava with characteristic no sweet, undissolved in cold water, form tickle gel in hot water. Tapioca produced from by some process :remove pell of cassava, cleaning, scraping, separation, precipitating, dryng, grinding and become tapioca. the aim of this research has amed to analyze the production of cornmeal by mass balance technology. the process of patiubikayu making by using cassava 2007 g and produces patiubikayu 376,2 g (with 14% water content).